2014
DOI: 10.1080/15435075.2014.889005
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Mesoporous Materials as Catalyst in Fast Pyrolysis of Wheat Straw

Abstract: In this study, wheat straw was chosen as a biomass sample and the fast pyrolysis of this sample was carried out with or without catalyst at different conditions in a well-swept fixed-bed reactor. Experiments were carried out in a well-swept tubular fixed-bed reactor with a heating rate of 300 • C/min, between pyrolysis temperature ranges 300-800 • C in the nitrogen atmosphere. The results indicated that a maximum oil yield of 31.9% was obtained at a pyrolysis temperature of 500 • C in non-catalytic procedure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Char and volatile yields for the different reactor temperatures after pyrolysis has finalized: experimental and literature (crosses), calculated (circles), volatile (pink and red), and char (black and blue).…”
Section: Resultsmentioning
confidence: 99%
“…Char and volatile yields for the different reactor temperatures after pyrolysis has finalized: experimental and literature (crosses), calculated (circles), volatile (pink and red), and char (black and blue).…”
Section: Resultsmentioning
confidence: 99%
“…Esters (EST) and methoxy-phenols (MPH) contained four members, respectively, while alcohols (ALC), sugars (SUG), acids (AC) and phenols (PH) contained 1-2 group members. PH and MPH are attributed to the decomposition of the lignin component of wheat straw, while anhydrosugars and smaller oxygenates result from the pyrolysis of hemicellulose and cellulose [60][61][62].…”
Section: Product Distributionmentioning
confidence: 99%
“…Recent studies involving both specific biomass class and MSW mixture revealed that the incorporation of acidic heterogeneous catalysts (such as zeolites) can produce aromatic compounds of compositions suitable for gasoline blends (i.e., BTEX: benzene, toluene, ethylbenzene, and xylenes) in a single step . The catalysts modify the yields of reaction products and perform bio‐oil upgrading in situ during the pyrolysis process.…”
Section: Gasification Technologies For Msw Upgrading To Syngasmentioning
confidence: 99%